Music, Culture and Society: Ideal Environments for Adults - Vernia-Carrasco, Ana M. (Cultural Arts Research and Development, 2022)
Music, as the backbone of artistic projects, can provide ideal spaces for adults, improving their quality of life. This proposal is part of a larger investigation, from a research stay. This research, of a synchronous and descriptive nature, used the narrative and descriptive perspective, but from the lived artistic experiences. Through interviews with experts, the desired information was obtained to write a report. The work was completed with a theoretical framework divided into different sections that include education, music and adults, didactic spaces for music education in adults, music and interculturality as an space for musical learning, and Sustainable Development Goals. The results confirmed the need to create spaces expressly for musical education and training for adults, regardless of whether or not they have previous musical training, since it is understood that adult profiles differ from children and adolescents, especially in terms of learning rhythms and needs. Among the conclusions, we can highlight the important relationship that is established between adults, society, music and culture. On the other hand, we are aware that there is a clear exclusion regarding access to artistic and cultural education.